SINERGITAS KEMITRAAN PEMERINTAH KABUPATEN DENGAN LAM SIAK (PENGELOLAAN DESTINASI ISTANA ASSERAYAH HASYIMIAH KABUPATEN SIAK TAHUN 2020-2021) - Putri Kholipah; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the synergy of the Regional Government of Siak Regency in managing Asseraya Al Hasyimiah Palace tourism and the obstacles in managing Asseraya Al Hasyimiah Palace tourism. The management of the Asseraya Al Hasyimiah Palace is carried out in synergy between the Tourism Office, LAM, and the people in Siak Regency. The Tourism Office as the main administrator plans the budget and actualizes the construction and operation of the Asseraya Al Hasyimiah Palace. This type of research is qualitative research, namely descriptive research. In this study, the authors took research at Asseraya Al Hasyimiah Palace Tourism, which is located in Kp Dalam, Siak District, Siak Regency. The informants in this study were the management of the Asseraya Al Hasyimiah Palace tourism manager, LAM Siak, the Tourism Office, and the local community. The results of this study indicate that the synergy of the Siak Regency Regional Government in managing Asseraya Al Hasyimiah Palace tourism is by forming partnerships with related parties such as the Culture Office, the Siak Malay Traditional Institute (LAM), and the local community and establishing partnerships through communication and coordination. In order to develop a synergistic relationship, good communication must be created, communication is carried out either directly or indirectly. Therefore, the synergy that is built apart from communication also needs coordination. Coordination in achieving something properly needed, must be there between related government agencies, the Culture Office, and the community and artists in Siakini Regency which is carried out through coordination meetings. The obstacle in managing Asseraya Al Hasyimiah Palace tourism lies in Human Resources (HR) and financial resources and the character of the community as beneficiaries of tourist attractions. Management of Asseraya Al Hasyimiah Palace requires training and additional human resources in improving professionalism in the field of tourism. Financial/funding is essential thing and works support system of this activity. No matter how good a plan or strategy is, if the funds needed to carry out historical tourism management activities are at minimum level, then the implementation will not be optimized, especially with the limited funds for managing historical tourism objects in the Kingdom of Siak. Keywords: Asseraya Al Hasyimiah Palace, Synergy, Tourism